Sensory Impact of Extended Maceration and Regulated Deficit Irrigation on Washington State Cabernet Sauvignon Wines - Casassa, Luis Federico; Larsen, Richard C.; Beaver, Christopher W.; Mireles, María S.; Keller, Markus; Riley, William R.; Smithyman, Russell; Harbertson, James F. (2018)
Irrigation practices such as regulated deficit irrigation (RDI) and winemaking practices such as extended maceration have been experimentally evaluated from a chemical perspective but their impacts on sensory composition and interactive effects merit scientific attention. This study evaluated the sensory impact of extended maceration applied to Cabernet Sauvignon grapes sourced from a vineyard subjected to four RDI treatments: replenishment of 100%, 70%, and 25% of full-vine crop evapotranspiration (ETc) from fruit set until veraison followed by 100% ETc until harvest (labeled 100% ETc, 70% ETc, and 25% ETc, respectively) and 25% ETc from fruit set to veraison followed by 100% ETc from veraison to harvest (labeled 25/100% ETc). Each RDI treatment was replicated four times (n = 4) and made into wine, with two replicates designated as controls (10 day skin contact) and two as extended maceration (30 day skin contact). Wines were evaluated by descriptive analysis with a trained panel (n = 15) and chemical and sensory data were correlated using canonical correlation analysis. Wine-perceived saturation and purple component ratings were highest in 25% ETc wines and were highly correlated with the concentration of flavonols, malvidin- and delphinidin-derivatives, and small polymeric pigments. Fruit-based aroma descriptors were highest in the 25/100% ETc and 70% ETc wines. Extended maceration increased perceived astringency and bitterness, which were in turn correlated with the concentration of flavan-3-ol and oligomeric proanthocyanidins. These results suggest that moderate RDI protocols such as 70% ETc and 25/100% ETc impact positively the fruity aroma component (black and red fruit), whereas extended maceration lowered fruity aromas, possibly due to the masking effect of the oxidized character perceived in these wines.